2000
DOI: 10.1046/j.1365-2613.2000.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status in delayed healing type of wounds

Abstract: This investigation studied the contribution of antioxidants in delaying healing in excision cutaneous wounds (8 mm) in diabetic, aged and immunocompromised animals. Skin levels of catalase, glutathione (GSH), ascorbic acid (AA) and vitamin E in streptozotocin-induced diabetic rat were lower as compared to nondiabetics. The 7-d wound tissue of diabetic rats showed an increased vitamin E level along with depleted GSH content. In aged rats (18 months old), higher levels of skin superoxide dismutase (SOD), glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(108 citation statements)
references
References 34 publications
4
97
1
6
Order By: Relevance
“…Studies have shown that ROS levels in wound tissues are significantly higher than normal tissues. 25 Here, we also observed that during wound healing, ROS was maintained at a high level for a long time.…”
Section: Discussionsupporting
confidence: 65%
“…Studies have shown that ROS levels in wound tissues are significantly higher than normal tissues. 25 Here, we also observed that during wound healing, ROS was maintained at a high level for a long time.…”
Section: Discussionsupporting
confidence: 65%
“…41 The magnitude of the generation of free radicals and their disposal mechanisms are known to be altered in burn patients, and some kind of correlation exists between altered free radical cascades and delayed wound healing. 20 In addition, Rasik and Shukla 42 showed that low levels of antioxidants accompanied by raised levels of markers of free radical damage played a significant role in delaying wound healing and that ROS produced in response to cutaneous injury impeded the healing process by causing damage to cellular membranes, DNA, proteins, and lipids; it was also shown that antioxidants promoted wound healing. 43 It was additionally reported that the administration of antioxidants enhanced the repair and healing process in cutaneous tissue; silymarin, the well-known antioxidant, was shown to be a useful agent for improving skin tissue regeneration and cutaneous healing.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes, aging, immunodeficiency, and malnutrition are typical causes for delayed wound healing. Under these pathological conditions, redox imbalance occurs, and elevated oxidative injury is observed [23].…”
Section: Roles Of Ros In Wound Healingmentioning
confidence: 99%